Transverse Stress Fracture of the Proximal Patella: A Case Report. Issue 6 (February 2016) - Atsumi, Satoru; Arai, Yuji; Kato, Ko; Nishimura, Akinobu; Nakazora, Shigeto; Nakagawa, Shuji; Ikoma, Kazuya; Fujiwara, Hiroyoshi; Sudo, Akihiro; Kubo, Toshikazu
Abstract : Abstract: Among stress fractures associated with sports activities, patellar stress fracture is rare. Regarding patella stress fractures, so far only distal transverse or lateral longitudinal fractures have been reported, but there are no reports of transverse fractures occurring in the proximal patella. We describe an extremely rare case of transverse stress fracture of proximal patella in a 9-year-old athlete. A 9-year old boy, who participated in sports (sprints and Kendo) presented with left knee pain without any external injury. In plain radiographs, a fracture line was observed in the proximal 1/3 of the left patella, and a patella stress fracture was diagnosed. For treatment, because 7 months of conservative therapy showed no improvement, internal fixation was carried out using Acutrak screws, and bone union was thus achieved. Three months after the operation, he was able to return to his previous level of athletic sports activity. Regarding the mechanism of onset, it is believed that the causes are longitudinal traction force and patellofemoral contact pressure. On the other hand, the contact region of the patella with the femur changes with the flexion angle of the knee. In the current case, the fracture occurred at a site where the patella was in contact with the femur at a flexion angle of >90°, so it is believed that it occurred as a clinical condition from being subjected to repeated longitudinal traction force and patellofemoral contact pressure at a flexion angle of >90°, during the sports activities of sprints and Kendo. The nonunion of the transverse stress fracture of his proximal patella was successfully treated with internal fixation using Acutrak screws.